Anomalous atmospheric refraction and comments on "fast and accurate determination of astronomical coordinates …" (Balodimos et al. 2003, Survey Review 37,290:269-275) - Hirt, Christian (Maney Publishing, 2012)
Balodimos et al. (2003, Survey Review, 37(290): 269–275) presented astrogeodetic instrumentation for the determination of astronomical coordinates, and stated an accuracy of ±0.01″ would be achieved within few hours observation time. However, these authors did not address anomalous atmospheric refraction, the effect of which is relevant for any accurate determination of astronomical latitude Φ and longitude Λ. This correspondence briefly reviews anomalous refraction and its effect on astrogeodetic methods, by first defining anomalous refraction, describing its origins, summarising results of theoretical and empirical studies, and giving ways to mitigate its effect. This demonstrates that anomalous refraction represents a major obstacle for determining astronomical coordinates (Φ,Λ) at the 0.01″ accuracy level from just a few hours of star observations, as claimed by Balodimos et al. (2003).